SWOT Analysis on Implementing Project Management Tool for Digitalization Media of Education Management - Rizqiya Windy Saputra (Universitas Pendidikan Indonesia (UPI), 2022)
School administration assignments is an important part of an education management system in school and a common complicated work in every start of education year especially for boarding-type schools. A School committee have to prepare many things related to students and teachers necessity, teachings materials, dormitories equipment and others in limitation of time. The lack of preparation time make some assignment can not fulfilled or delivered on determination time. In this research, not only many cases will be identified from teachers and schools committee related to effectiveness in maximizing their time to finish their assignments, but also SWOT analysis as a strategic planning and management technique usually used to help a person or organization identify Strengths, Weaknesses, Opportunities, and Threats will be conducted in this area. SWOT analysis will be combine with project management tool to organize the teachers and school committee assignments. This paper supposed to explore many advantages from project management tool that can generate new perspective in managing complicated administration works. The exploration is carried out using the SWOT analysis method to school administrative management. And finally, this papers can proposed a new assignment model and framework in boarding school type to increase their work effectiveness and reduce wasted time.